LEGAL IMPLICATIONS OF NON-COMPLIANCE WITH THE DECISION OF THE STATE ADMINISTRATIVE COURT IN TERMS OF THE IMPLEMENTATION OF REGIONAL AUTONOMY AND THE UNITARY STATE - Dinata, Ari Wirya (Jurnal Hukum Peratun, 2021)
Implementation of rule of law in Indonesia takes the consequences to establishing the state administrative court. The state administrative court as a legal institution is a manifestation check and balance principle. So that the government does not commit arbitrary action or does not abuse of their power. Administrative court is a place to assess if there are acts of state administrative bodies / officers are not based on the laws and regulations of general principles of good governance or even harm the community. As a respected judicial institution (state administrative court), the decision of the state administrative court must be respected and implemented by each party. In practice, however, there are a number of non-compliance committed by state administrative bodies / officials. They are opposed to carrying out the decision of the state administrative court despite having a legally binding verdict. Therefore, this writing tries to comprehensively discuss the causes of non-compliance by state agencies or administrators. Furthermore, this study also discusses the legal implications that occur if the state administrative agency / official still ignores the court’s decision according to the prevailing laws and regulations. The next study discusses the relationship between central government and local government in the framework of regional autonomy is associated with non-compliance that occurred. For as it is known that the President as head of government holds full power to run the government and ensure all policies implemented by the local government even more so in the concept of a unitary state.